IMPLEMENTASI AJARAN ASAH ASIH ASUH PADA PEMBELAJARAN DARING MATA KULIAH KARAWITAN DI MASA PANDEMI COVID-19 DITINJAU DARI AJARAN TAMANSISWA - Setyawan, Arya Dani; Masjid, Akbar Al; Trisharsiwi, Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
The impact of the Covid-19 pandemic has almost affected all human activities in this world, one of which is the field of education. Various strategies in fulfilling education are implemented through an online system according to the health protocol recommended by the government. The strengths and weaknesses of the implementation of education using this online system are dynamic in itself for both tutors and students. This study aims to review how the process of implementing education using an online system. As researchers and practitioners of education, the implementation of learning with this online system has its challenges because it cannot meet face to face directly but the material presented must be understood by students. Tamansiswa in this case still inherits the teachings of Ki Hadjar Dewantara which in its implementation are very useful in online learning needs. The method of honing, loving, fostering in the implementation of learning is expected to be an effective strategy for the implementation of learning. This study uses a descriptive qualitative research approach so that researchers can describe and answer problems of a current phenomenon or event. Regarding the implementation of learning with an online system, the researcher uses one of the concepts of Ki Hadjar Dewantara's teachings, namely sharpening, compassion, fostering in single variables as well as correlation and/or comparison of various variables. It can be understood that the descriptive research method is a method used to tell the situation in the field supported by facts obtained by observing and examining in-depth to find understanding and the truth of the data.